2021
DOI: 10.3390/ph15010050
|View full text |Cite
|
Sign up to set email alerts
|

Phytochemical Profile and Biological Activities of the Extracts from Two Oenanthe Species (O. aquatica and O. silaifolia)

Abstract: This study presents the evaluation of biological activities and chemical profiling of Oenanthe aquatica (L.) Poir. and Oenanthe silaifolia M. Bieb. The phytochemical profile, antioxidant, enzyme inhibitory, cytotoxic and antiviral activities of the methanolic and aqueous extracts were investigated. The aqueous extract of O. aquatica possessing the highest content of phenolics (60.85 mg gallic acid equivalent/g extract), also exhibited the strongest radical scavenging potential against 2,2-diphenyl-1-picrylhydr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
14
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(14 citation statements)
references
References 53 publications
0
14
0
Order By: Relevance
“…Nowadays, with cholinesterase inhibition being the most widely used approach for the treatment of Alzheimer’s disease, several efforts have been made to discover new sources of inhibitors. Different plants have been tested to understand their effects on AChE [ 56 , 57 , 58 ]. Indeed, flavonoids and phenolic acids have been reported to fit into the gorge of the active site of the enzyme [ 59 ].…”
Section: Resultsmentioning
confidence: 99%
“…Nowadays, with cholinesterase inhibition being the most widely used approach for the treatment of Alzheimer’s disease, several efforts have been made to discover new sources of inhibitors. Different plants have been tested to understand their effects on AChE [ 56 , 57 , 58 ]. Indeed, flavonoids and phenolic acids have been reported to fit into the gorge of the active site of the enzyme [ 59 ].…”
Section: Resultsmentioning
confidence: 99%
“…We have previously reported that Oenanthe aquatica and Oenanthe silaifolia extracts possess significant antiviral activity, and the observed effect may be related to the presence of caffeic acid and its derivatives (caffeic acid glucoside, chlorogenic acid, cryptochlorogenic acid, and neochlorogenic acid) present in those extracts [ 52 ]. Interestingly, caffeic acid derivatives were identified in the FLM, which showed the highest anti-HHV-1 activity, and in FSBI, which exerted a noticeable, though much lower, influence on the tested herpes virus, reducing the infectious titer only by 0.92 log.…”
Section: Resultsmentioning
confidence: 99%
“…The evaluation of cytotoxicity was performed against normal kidney fibroblasts (VERO) and cancer cell lines derived from cervical adenocarcinoma (HeLa) and colon cancer (RKO) using microculture tetrazolium assay (MTT) as previously described [ 52 ]. Briefly, the cell monolayers were incubated with serial dilutions of the tested extracts for 72 h, and then cellular viability was assessed using the MTT protocol.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…It will contact the rest of the solvent, thus obtaining a new amount of extractive solution. The two extractive liquids will combine and filter after a 24-h rest [21].…”
Section: Introductionmentioning
confidence: 99%